Human Growth Hormone: The Dilemma of Expanded Use in Children - White, Gladys B. (Kennedy Institute of Ethics journal, 1993)
In the specialized area of pediatric endocrinology, the use of human growth hormone (hGH) both for children who have a growth hormone abnormality and for the treatment of non-hGH-deficient children who are short is a current clinical reality that raises important ethical questions. Generally speaking, the use of hGH for those children who are clearly lacking it is an efficacious intervention based upon established clinical criteria. The use of hGH for children who are short, but have no growth hormone abnormality is ethically and clinically more controversial. The moral conundrum of how to gain knowledge about new medical treatments that may be beneficial to children while, at the same time, ethically enrolling them in clinical trials with placebo arms in order to gain such knowledge will continue to be a contentious issue in the conduct of research and in the delivery of health care. In addition, there are questions about what ought to be studied and whether a physical characteristic such as short stature ought to be viewed as a circumstance of less than optimal health.